Application of Box–Behnken design for processing of mefenamic acid–paracetamol cocrystals using gas anti-solvent (GAS) process. (July 2018) - Wichianphong, Napada; Charoenchaitrakool, Manop
Graphical abstract: Highlights: Cocrystals of mefenamic acid with paracetamol were produced by GAS process. Box–Behnken design was used to optimize the GAS process parameters. PAR-to-MEF ratio and %MEF saturation were significant variables. Cocrystals by GAS could dissolve 2.3 times faster than marketed combination drugs. Cocrystals by GAS could dissolve 5.3 times faster than those by slow evaporation. Abstract: The present work deals with the preparation of drug–drug cocrystals of mefenamic acid (MEF) with paracetamol (PAR) using gas antisolvent (GAS) process with an aim to improve the dissolution rate of MEF. Box–Behnken experimental design was used to optimize the GAS process variables for minimal dissolution time of MEF. A mathematical model was developed to study the effects of operating temperature, PAR-to-MEF molar ratio and %MEF saturation in the ranges of 25 °C–45 °C, 3:1–5:1 and 70–90%, respectively. PAR-to-MEF ratio and %MEF saturation were found to be the main parameters affecting the dissolution time. The fastest dissolution time (t63.2 ), 11.38 min, was obtained at the optimal conditions of a temperature of 34.9 °C, PAR-to-MEF ratio of 4.3:1 and MEF saturation of 86.8%. Optimized cocrystals by GAS showed that the dissolution rate of MEF improved by 6.0, 5.3 and 2.3-fold when compared to pure MEF, sieved cocrystals prepared by a traditional slow evaporation technique and sieved marketed combination drugs, respectively. GAS cocrystallization thus offers an efficient way to enhance the dissolution rate of the poorly water-soluble drug.